Razvoj športne vzgoje in športa na Fakulteti za strojništvo od začetkov do danes - Bratuž, Žiga (Šport (Ljubljana), 2019)
Faculty of Mechanical Engineering has a rich history of incorporating sports activities into the study program. Since 1963 the Faculty has been offering their students a lot of sports contents, compared to other faculties of University of Ljubljana. These contents have a high approval rate with the Faculty leadership, as well as with the students. Even after the Bologna reform, when a lot of faculties cut Physical Education from their curriculum, the Faculty of Mechanical Engineering retained it as a part of the program. Sport is becoming an increasingly important component of personal development, as it represents a counterweight to the sedentary lifestyle, which is caused by our technological development. At the Faculty of Mechanical Engineering we are going to strive for the improvement of the conditions for exercising and the rise of the number of physically active students. We hope that the University of Ljubljana finds a systemic solution for the position of Physical Education at the University and that it becomes a part of the program at all the faculties once again.
Keywords: Faculty of Mechanical Engeneering; Fakulteta za strojništvo; physical education; sport; students; šport; športna vzgoja; študenti; University of Ljubljana; Univerza v Ljubljani